Tension forces in stud connectors between concrete slabs and steel girders under transverse bending moments. (April 2022) - Xiang, Da; Liu, Yuqing
Abstract: In steel–concrete composite bridges, stud connections between steel girders and concrete slabs can be subjected to transverse bending moments, where noticeable tension forces may arise in stud connectors near transverse stiffeners of steel webs. Wider cantilevers further enhance these effects. This paper seeks to propose a practical calculation method of tension forces in stud connectors under transverse bending moments and clarify the influential factors on tension forces. Firstly, the equilibrium equation of moments is established for the stud connection considering the contributions of tension forces ( T ), contact forces ©, and prying forces ( p ). Thereafter, the relations between T and p are built through a cantilever beam model, and the position of c is determined by extensive finite-element (FE) analysis. Subsequently, an engineer-friendly calculation procedure is introduced and validated against FE results, and the effects of various parameters are discussed through a parametric analysis. Results indicate that the proposed method reveals satisfactory accuracy and produces safe predictions in most cases. It also successfully captures the influences of geometric parameters of the stud connection and the stud's tensile stiffness. By reducing the longitudinal and transverse spacings between studs, and increasing the thickness of top flange, the maximum tension force ( T 11 ) can be significantly decreased by up to 33%, 36%, and 46%, respectively. Reductions in stud's tensile stiffness can also lower T 11, while the effects are relatively minor with the largest drop of 10%. Decreases in the distance from the stud to the stiffener can enlarge T 11 by 63% at most.